ANALISIS BIBLIOMETRIK: MANAJEMEN RANTAI PASOKAN HIJAU (2023-2014): - Wahyuni, Hilda; Haryati, Teti; Yudha Heryawan Asnawi (Universitas Airlangga, 2024)
This research discusses the publication trend on the topic of green supply chain management with